Influence of raw materials composition on firing shrinkage, porosity, heat conductivity and microstructure of ceramic tiles. Issue 1 (April 2016) - Kurovics, E; Buzimov, A Y; Gömze, L A
Abstract: In this work some new raw material compositions from alumina, conventional brick-clays and sawdust were mixed, compacted and heat treated by the authors. Depending on raw material compositions and firing temperatures the specimens were examined on shrinkage, water absorption, heat conductivity and microstructures. The real raised experiments have shown the important role of firing temperature and raw material composition on color, heat conductivity and microstructure of the final product.